To the 80th Anniversary of Professor Kalakura Ya.S. and the 55th Anniversary of His Scientific and Pedagogical Activity - Volodymyr Velykochyy; Serhiy Derevjanko; Pavlo Vychivskyi (Vasyl Stefanyk Precarpathian National University, 2019)
The article includes the main stages of life and scientific achievements of Professor Yaroslav Stepanovych Kalakura. The executions of this prominent historian and his scientific achievements are analyzed. It is considered his personal contribution to the development of Ukrainian historical science, in particular, in historiography, source studies and archival studies.